A promising unisource thermal evaporation for in situ fabrication of organolead halide perovskite CH3NH3PbI3 thin film. (4th June 2015) - Liang, Guang‐Xing; Fan, Ping; Luo, Jing‐Ting; Gu, Di; Zheng, Zhuang‐Hao
Abstract: In this work, a new method of fabricating organolead halide perovskite CH3 NH3 PbI3 thin film by unisource thermal evaporation was proposed, which ensured high‐quality film with composition, crystal‐structure homogeneity, full surface coverage, well‐defined grain structure, high crystalline, and reproducibility, suggesting its promising applicability for significant optimization in efficient. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : A new method of fabricating organolead halide perovskite CH3 NH3 PbI3 thin film by unisource thermal evaporation was proposed. High level of tetragonal phase‐purity and crystallinity of CH3 NH3 PbI3 thin film with stoichiometry after in situ annealed could be found. Good uniformity, reproducibility, and simple setup were required.